Artificial intelligence and surgical innovation: lower limb arthroplasty. (2nd October 2020) - Magan, AA; Kayani, B; Chang, JS; Roussot, M; Moriarty, P; Haddad, FS
Abstract : The number of patients requiring hip and knee arthroplasty continues to rise each year. Patients are living longer and expecting to remain active into later life following joint replacement. Developments in computer-assisted surgery and robotic technology may optimise surgical outcomes and patient satisfaction following lower limb arthroplasty. The use of artificial intelligence in healthcare is rapidly growing and has gained momentum in lower limb arthroplasty. This article reviews the use of artificial intelligence and surgical innovation in lower limb arthroplasty, with a particular focus on robotic-assisted surgery in total knee arthroplasty.